The AIDS Pandemic Searching for a Global Response - Merson, Michael (Springer International Publishing, 2018)
This ambitious book provides a comprehensive history of the World Health Organization (WHO) Global Programme on AIDS (GPA), using it as a unique lens to trace the global response to the AIDS pandemic. The authors describe how WHO came initially to assume leadership of the global response, relate the strategies and approaches WHO employed over the years, and expound on the factors that led to the Programme's demise and subsequent formation of the Joint United Nations Programme on HIV/AIDS (UNAIDS). The authors examine the global impact of this momentous transition, portray the current status of the global response to AIDS, and explore the precarious situation that WHO finds itself in today as a lead United Nations agency in global health. Several aspects of the global response - the strategies adopted, the roads taken and not taken, and the lessons learned - can provide helpful guidance to the global health community as it continues tackling the AIDS pandemic and confronts future global pandemics. Included in the coverage: ·The response before the global response ·Building and coordinating a multi-sectoral response ·Containing the global spread of HIV ·Addressing stigma, discrimination, and human rights ·Rethinking global AIDS governance ·UNAIDS: finding its place in congested waters The AIDS Pandemic will find an engaged audience among policymakers, students, faculty, journalists, researchers, and other health professionals working and interested in global health, public health, the World Health Organization, HIV/AIDS, global pandemics, the history of medicine, and global health policy. It will also interest those involved in international relations, international development, global affairs and governance, the United Nations, and NGOs.